Increasing litter size in swine herds - Duane L Davis; Jeffrey S Stevenson; J Ernest Minton (Kansas Agricultural Experiment Station Research Reports, 1987)
Management and biological factors combine to limit litter size in swine herds. With present technology, improving litter size depends upon increasing the number born in the first litter and prolonging sow longevity. Methods for improving size of the first litter rely on increasing the number of eggs ovulated and include flushing (increased feed for at least 10 days before breeding), selecting breeds with high ovulation rates, and delaying breeding until after the pubertal or first estrus. The first two methods are the most cost effective under farm conditions. Because litter size peaks at the fourth or fifth litter, it is also important to increase the proportion of multiparous sows in the herd. This can be accomplished by not culling sows as long as they are productive.; Swine Day, Manhattan, KS, November 19, 1987
Keywords: Swine day; 1987; Kansas Agricultural Experiment Station contribution; no. 88-125-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 528; Swine; Litter size; Longevity